La carga de la prueba en el proceso penal contra las personas jurídicas - Reyna Alfaro, Luis Miguel (2024)
This research analyzed the question of the burden of proof in the criminal procedure to legal entities provided by Ley Nº 30424. Our general approach is that the difficulties of criminal prosecution against legal entities cannot affect the right of presumption of innocence.